Genital Tract Infection during Pregnancy and its Association with Preterm Delivery - Susilawati, Tri Nugraha; Satria, Yohanes Aditya Adhi (Institute of Topical Disease Universitas Airlangga, 2021)
Genital tract infection (GTI) remains a significant health concern. It is estimated that in 2016, there were 370 million people who suffer from chlamydia, gonorrhea, and trichomoniasis; and 708 million others suffer from genital herpes and condyloma acuminatum. It has been reported that in pregnant women, GTI is associated with preterm delivery. The mechanisms of GTI-associated preterm delivery need to be further understood to prevent neonatal mortality and morbidity that could be the risk factor for neonates' growth and development disorders. This article aims to describe various types of GTI and the associated pathogenesis causing preterm birth. A literature search was conducted to retrieve recent articles published in English from online databases including Pubmed, ScienceDirect, and Google Scholar. This literature study found that GTI evokes inflammatory responses that trigger several mechanisms leading to preterm delivery. The inflammatory responses in GTI include the production of proinflammatory cytokines and robust activation of neutrophils. The key mechanisms that stimulate preterm delivery in GTI include the events of early uterine contraction, preterm premature rupture of membranes, and induction of cervical ripening; which are under normal circumstances in a full-term pregnancy, those mechanisms are regulated by progesterone and prostaglandin levels along with suppression of the inflammatory responses. In conclusion, this paper has described the underlying mechanisms of preterm delivery in pregnant women with ISG. However, such mechanisms remain unclear in candida and gonococcal infection; thus, prompting the need for further studies.